Comparative characteristics of methods of allergological examination for house dust mite allergy in children with bronchial asthma and allergic rhinitis - O. V. Trusova; A. V. Kamaev; N. L. Lyashenko; I. V. Makarova; N. B. Platonova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Objective. To determine the diagnostic significance of methods of allergological diagnostics: skin prick tests (SPT), quantitative determination of specific immunoglobulin E (sIgE) and nasal provocative test (NPT) in children with allergy to house dust mites (HDM) diagnosed with allergic rhinitis (AR) or AR in combination with asthma.   Methods. Patients underwent a targeted history taking for possible domestic sensitization, SPT with HDM allergens, NPT with HDM, and sIgE to HDM allergens was determined by the ImmunoCAP method.   Results. The statistical processing group included 109 children (67 boys, 42 girls, aged 5 to 17,9 years (mean age 8,9 ± 2,52 years)), in whom sensitization to HDM was confirmed by at least one of the methods used in the study. A higher sensitivity of SPT then of sIgE was determined (96,3 % and 81,6 %, respectively). According to SPT and sIgE results, sensitization to both types of mites (D. pteronyssinus and D. farinae) is more common than isolated. Coincidence of positive results of SPT and sIgE was obtained in 84 cases (77,1 %).   Conclusion. SPT can be considered as the first line of investigation. The use of a complex of examination methods is necessary to determine the role of sensitization to HDM, if NPT is taken as the «gold» standard of diagnosis.